International Business after Brexit: The Impact on Taxes - Ernesto Marco BAGAROTTO; Francesca DAL MAS (Communications of International Proceedings, 2020)
The Brexit is the exit of the United Kingdom from the Europen Union. After a transitional period, as of January 1st, 2021, a new set of rules will apply. Still, there are several open issues which need to be addressed. The present paper analyses the impact of the Brexit on taxes, which is going to affect the international business for organizations operating both in the European Union territory and in the United Kingdom.
Keywords: Brexit; European Union; International Business; Taxes.